In vitro effect of Withania somnifera, AYUSH-64, and remdesivir on the activity of CYP-450 enzymes: Implications for possible herb−drug interactions in the management of COVID-19 - Kasarla, Siva Swapna; Borse, Swapnil P.; Kumar, Yashwant; Sharma, Neha; Dikshit, Madhu (Frontiers in Pharmacology, 2022)
Ayurvedic medicines Withania somnifera Dunal (Ashwagandha) and AYUSH-64 have been used for the prevention and management of COVID-19 in India. Present study explores the effect of Ashwagandha and AYUSH-64 on important human CYP enzymes (CYP3A4, CYP2C8, CYP2D6) to assess their interaction with remdesivir, a drug used for COVID-19 management during the second wave. The study also implies possible herb-drug interactions (HDIs), as Ashwagandha and AYUSH-64 are being used for managing various pathological conditions. Aqueous extracts of Ashwagandha and AYUSH-64 were characterized using LC-MS/MS. A total of 11 and 24 phytoconstituents were identified putatively from Ashwagandha and AYUSH-64 extracts respectively. In addition, in-silico studies revealed good ADME properties of most of the phytoconstituents of these herbal drugs and suggested that some of these might possess CYP-450 inhibitory activity. In-vitro CYP-450 studies with human liver microsomes showed a moderate inhibition of CYP3A4, 2C8, and 2D6 by remdesivir, while Ashwagandha had no inhibitory effect alone or in combination with remdesivir. AYUSH-64 also exhibited a similar trend however a moderate inhibitory effect on CYP2C8 was noticed. Thus, Ashwagandha seems to be safe to co-administer with the substrates of CYP3A4, CYP2C8, and CYP2D6. Perhaps caution is however warranted in prescribing AYUSH-64 along with CYP2C8 substrate drugs. Further preclinical and clinical PK studies would be helpful for their effective and safer use in the management of various ailments along with other drugs.